Teachers' Pedagogical Skills and Students' Learning of English Language in Oruk Anam Local Government Area of Akwa Ibom State, Nigeria - PRINCEWILL I. EGWUASI; NNENNA F. NNODI; ANIEFIOK S. UDOATAI (Dr. Chinmay Pandya, 2019)
An investigation into teachers' pedagogical skills and students' learning of English Language in public secondary schools in Oruk Anam Local Government Area of Akwa Ibom State was carried out. Three major variables namely; teachers' classroom management skill, teachers' lesson delivery skill, and teachers' level of communication, were studied to show how it relates with students' learning of English Language. Three research questions and three research hypotheses were raised. The research adopted a descriptive survey approach using a researchers' designed questionnaire titled teachers' Pedagogical Skills and Students' Learning of English Language Questionnaire (TPSSLELQ) with reliability coefficient of 0.857 to collect data from 130 respondents from 10 secondary schools in Oruk Anam Local Government Area of Akwa Ibom State. Pearson Product Moment Correlation (PPMC) was used to test all the hypotheses at 0.05 level of significance. The result of the study revealed that teachers' classroom management skill, teachers' lesson delivery skills, and teachers' level of communication, have a significant relationship on students' learning of English Language. The study recommended among others that teachers should evaluate their lessons at every point as it provides feedback so that students' misconceptions may be clarified. Also, educational stakeholders should take the training and retraining of teachers seriously to boast their competence and managerial skills as it is shown to have a positive relationship on students' learning of English Language.